Synthesis Of Mg/Al Hydrotalsite-Magnetite As CN- Ion Adsorbent On Wastewater Tapioca Industry - Maudi Aulia; Fajar Indah Puspita Sari; Ristika Oktavia Asriza (Department of Chemistry - Universitas Bangka Belitung, 2021)
Cyanide compounds contained in tapioca industrial wastewater are relatively high, so it is necessary to reduce cyanide levels. This study utilizes the hydrotalcite-magnetite ability to adsorption of CN- ions. The composite formation process is carried out by mixing the magnetite phase at the stage of hydrotalcite-magnetite synthesis. The characterization of X-Ray Diffraction (XRD) shows reflection of the magnetite peak of 2θ 21.42°; 30,28°; 33.40°;35.65° and 37°. While the peak of hydrotalocites at an angle of 11.66° ; 23,33° ; 34,80° ; 60,92° ; and 62.21°. This result is supported by ir spectra on hydrotalocytes shown by O-H group at wave number 3441 cm-1, O=C-O at wave numbers 1359 cm-1, M-O and M-OH at wave numbers 964 cm-1, 797 cm-1 and 673 cm-1. Fe-O and Fe-OH absorption from magnetites at wave numbers 892 cm-1, 798 cm-1 and 629 cm-1. 0.4 grams of hydrotalcite-magnetite at 30 minutes of stirring absorbed 0.0490 mg/L of cyanide from tapioca liquid waste solution. The value of adsorption capacity is 0.022 mg/g and the adsorption efficiency is 87.96%. The hydrotalcite-magnetite adsorption method is superior to aerob and anaerobic methods using bacteria in the tapioca industry.